A STUDY ON PHYTOCHEMICAL SCREENING, ANTIOXIDANT, ANTIMICROBIAL AND Î±-Î‘MYLASE INHIBITORY ACTIVITIES OF CRUDE EXTRACTS OF THE STEM BARK OF PISONIA GRANDIS, R.BR - Mohan, Vishu; Ramasamy, Mohan Kumar; Vemuri, Srikalyani; Kaliappan, Ilango (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of the present study is to determine the phytochemical screening, antioxidant activity and Î±-amylase inhibitory activity of the crude hexane, ethyl acetate and ethanolic stem bark extract of Pisonia grandis. Methods: The evaluation of antioxidant and antimicrobial activity, total phenolic, and flavonoid content were assessed using 2,2-diphenyl-1- picrylhydrazyl, Folinâ€“Ciocalteu's reagent, and aluminum chloride assay, respectively. The antidiabetic activity was assessed for porcine pancreatic Î±-amylase for the stem bark of P. grandis. Results: Phytochemical screening confirmed the presence of phenolic, flavonoids, tannins, saponins, terpenoids, and steroids in all the three extracts. The antioxidant activity showed 148.2 Î¼g/ml, total phenolic content (gallic acid equivalent), 0.0665Â±0.0002 mg/g, flavonoid content (quercetin equivalent), 0.6061Â±0.1817 mg/g, and inhibitory concentration 50% values were found to be 40.42 Î¼g/ml and showed better in ethyl acetate extract. The antidiabetic activity exhibited mimic action with insulin due to the presence of pinnatol in the stem bark and leaves of P. grandis. Conclusion: P. grandis stem bark crude ethyl acetate extract showed strong antioxidant activity, high phenolic, and flavonoid content. The antimicrobial activity was studied in both Gram-positive and Gram-negative strains against ampicillin and rifampicin as reference drugs. Antidiabetic activity shows effective result by Î±-amylase inhibitory activity.